Learning Methods of “Kitab Kuning” in Dayah Manyang Gampong Meulum Samalanga District - Helmi; Amiruddin; Zahrul Mubarrak; Siti Hajar; Saldiani (Britain International for Academic Research (BIAR) Publisher, 2021)
One of the oldest dayahs in the Masjid Raya area of Samalanga District is Dayah Manyang Gampong Meulum and in recent years the wheels of education have been renewed by adding formal education in the form of lectures from IAI Al-Aziziyah Samalanga, but the salafiyah education system is still running. Seeing the current phenomenon in the dayah, the author tries to further examine the yellow book learning method in a scientific paper entitled Learning Management of the Kitab Kuning in Dayah Aceh ”(Case Study of Dayah Manyang Gampong Meulum Samalanga). There are three problem formulations in this scientific paper, the first is how the management method of the yellow book learning planning at Dayah Manyang Gampong Meulum Samalanga, the two management methods of learning the yellow book and finally what are the obstacles in learning the yellow book in the Dayah. The approach used in this research is qualitative using descriptive analysis method. The results showed that Dayah Manyang in the yellow book learning method adopted the bandongan (syarah) method where the teacher explained the book and its contents to their students and the students only listened carefully, wrote the translation and understood it. Another method is sorogan, which is the opposite of bandongan, this method is that the students are more active in learning and come to the teacher to read the book in front of the teacher. The last method is the rote method which focuses on memorizing verses and other types of memorization by students. Furthermore, the obstacles faced in yellow kitav learning revolve around the lack of discipline of the students so that time is not paid attention and causes drowsiness while studying. The lack of private tutors or guree peulang is also an obstacle in addition to very low management science, only armed with natural expertise. Lack of interest in learning is also an obstacle. Hopefully there will be a change towards the better for the advancement of the Dayah Manyang Gampong Meulum Samalanga education.